KAJIAN PERUBAHAN JERAPAN DAN KETERSEDIAAN P PADA TANAH ULTISOL DENGAN PEMBERIAN LIMBAH KELAPA SAWIT (The Study of P Adsorption and Availability Changes on Ultisols with the Granting of Oil Palm Wastes) - D., Pertiwi,; Y., Sulistiyanto,; Z., Damanik, (AGRIPEAT, 2017)
ABSTRACTThe purpose of this research is to know the influence of the incorporation TKKS and boilerashes best doses in lowering adsorption P and increase the availability of P and pH on Ultisols.This study used a Randomized Complete Design (RAL) consisting of 2 factorial factortreatments. First factor was TKKS (T) consists of three doses of treatment i.e: T0 : 0 ton.ha-1,T1 : 20 ton.ha-1 dan T2 : 40 ton.ha-1. Second Factor was Boiler Ash (A) consists of three dosesof treatment i.e: A0 : 0 ton.ha-1, A1 : 11,6 ton.ha-1 dan A2 : 23,2 ton.ha-1. The results showedthat combination treatment of empty oil palm bunches (TKKS) and boiler ashes on ultisols hasraised pH H2O, raised and lowered ÎpH when the dose increased, and lowered exchangeable Al.Whereas single TKKS factor treatment and boiler ash raise pH KCl. Single factor Treatment ofboiler ash increases P-available with the best dose treatment i.e. A2 (23,2 ton ha-1), it alsoincreases the coefficient of bonding energy and lowering the site adsorption namely treatmentA1 (11,6 ton.ha-1) and A2 (23,2 ton.ha-1), while the single factor treatment of TKKS improves Padsorption maximum i.e. treatment T1 (20 ton.ha-1), but lose the P adsorption maximum i.e.treatment T2 (40 ton.ha-1).Keywords : P adsorption, P availability, Oil Palm Waste, Ultisols.